Penerapan Fungsi Regulatif dalam membentuk Lembaga Penyiaran Peduli Covid 19 di Kota Bandung - Zaki Ramdhani; Dede Lilis (UNISBA Press, 2022)
Abstract. Television and radio have become consistent broadcast media and are still enjoyed by the Kompas.com media portal published on August 22, 2020, revealing that according to KPI, 89% of people trust the internet more. In a pandemic, massive information reveals about Covid-19, how does the mass media keep reminding them to comply with health protocols that have been standardized and improved by the government in order to break the chain of virus spread. The purposes of this study (1) are to declare the care for Covid 19 broadcast by MGT Radio, (2) to describe the content of caring for Covid 19 broadcasts, (3) to describe the regulation by KPID of West Java Province. This research method uses a qualitative research method with a constructivist paradigm, case study approach, data collection obtained by researchers obtained by means of in-depth interviews, observations, documentation, literature studies both from books, journals and from the internet, data analysis through data collection, data reduction, Presentation of data, Drawing Conclusions, Validity techniques through Source Triangulation Techniques. Informants in this field of research are the Commissioner for Institutional KPID and Broadcast Content and representatives from the MGT FM Radio Bandung Broadcasting Institution. The determination of informants in this study was based on purposive sampling. The results of the study show that the implementation of the regulatory function in establishing the Covid 19 care Broadcasting Institution in Bandung City is quite good, how does the Broadcasting Institution implement the Central KPI circular letter No. 156/K/KPI/31.2/03/2020 By forming programs that are needed by the community today and through routine pro-health appeals and the application of health programs in the office environment, the West Java Provincial KPID also conducts supervision through community complaints, West Java PIS and action if there are Broadcasting Institutions those who violate these rules, this is applied as a preventive measure from the KPI and because the Broadcasting Institution has social responsibility and as a means of education and concern for the community in the COVID-19 pandemic situation. From the monitoring of the West Java Province KPID, Broadcasting Institutions, especially in the City of Bandung, have implemented rules properly and there are no violations of regulations related to the existence of these rules. Abstrak. Televisi dan Radio menjadi suatu medium penyiaran yang konsisten dan masih ramai dikonsumsi oleh portal media kompas.com yang dimuat pada tanggal 22 agustus 2020 memberitakan bahwasanya menurut KPI 89% masyarakat lebih percaya televisi dibandingkan internet. Pada kondisi pandemi sekarang informasi-informasi masif memberitakan mengenai Covid-19, bagaimana media massa tidak henti-hentinya mengingatkan agar mematuhi protokol Kesehatan yang sudah standar dan dianjurkan oleh pemerintah agar memutus rantai penyebaran virus. Tujuan dari penelitian ini (1) Untuk mendeskripsikan penerapan regulasi penyiaran peduli Covid 19 oleh MGT Radio, (2) Untuk mendeskripsikan alasan regulasi penyiaran peduli Covid 19 perlu diterapkan, (3) Untuk mendeskripsikan Pengawasan regulasi tersebut oleh KPID Provinsi Jawa Barat. Metode Penelitian ini menggunakan Metode Penelitian Kualitatif dengan paradigma Konstruktivis, pendekatan Studi Kasus, Pengumpulan Data yang diperoleh peneliti didapatkan dengan cara wawancara mendalam, observasi, dokumentasi, studi literatur baik dari buku, jurnal maupun dari internet, Analisis data melalui pengumpulan data, reduksi data, Penyajian data, penarikan kesimpulan, Teknik keabsahan melalui Teknik Triangulasi Sumber. Informan dalam penelitian ini yaitu Komisioner KPID bidang Kelembagaan dan Isi Siaran serta perwakilan dari Lembaga Penyiaran MGT FM Radio Bandung, Penentuan informan dalam penelitian ini adalah berdasarkan purposive sampling. Hasil Penelitian bahwa penerapan fungsi regulatif dalam membentuk Lembaga Penyiaran peduli Covid 19 di Kota Bandung sudah cukup baik, bagaimana Lembaga Penyiaran menerapkan surat edaran KPI Pusat No. 156/K/KPI/31.2/03/2020 dengan membentuk program yang dibutuhkan oleh masyarakat saat ini serta melalui rutinitas himbauan prokes dan penerapan prokes dilingkuan kantor, KPID Provinsi Jawa Barat juga melakukan pengawasan melalui aduan masyarakat, PIS Jabar dan penindakan jika ada Lembaga Penyiaran yang melanggar aturan tersebut, hal tersebut diberlakukan sebagai Tindakan preventif dari KPI serta karena Lembaga Penyiaran memiliki tanggung jawab sosial dan sebagai sarana edukasi dan kepedulian kepada masyarakat disituasi pandemi covid 19. Dari hasil pemantauan KPID Provinsi Jawa Barat, Lembaga Penyiaran khususnya di Kota Bandung sudah menerapkan aturan dengan baik dan tidak ada intensitas pelanggaran siaran terkait dengan adanya aturan tersebut.